Earnings Management: Do Firms Play “Follow the Leader”? - Bratten, Brian; Payne, Jeff L.; Thomas, Wayne B. (Contemporary Accounting Research, 2016)
Abstract In this study we examine whether the reported performance of one firm affects the discretionary reporting behavior of another firm. We do this by identifying the leader within each industry, defined as the first large announcing firm. We find that the discretionary performance of followers (those firms announcing after the leader) relates positively to the leader's reported performance. Specifically, when the leader misses analysts’ expectations, followers report lower discretionary accruals, have fewer income‐decreasing special items, and are less likely to meet analysts’ expectations. In contrast, when leaders report good news, followers report higher discretionary accruals and are more likely to meet expectations (although we do not find evidence of a positive association between leaders’ good news and followers’ income‐decreasing special items). Overall, the results are consistent with managers of followers perceiving that earnings news of the leader will affect investors’ and others’ performance expectations for their firms.